‘Greenwashing’ tobacco products through ecological and social/equity labelling: A potential threat to tobacco control - Houghton, Frank (Tob Prev Cessat, 2018)
There has been significant growth in ecological/environmental labelling of products and services internationally in recent years. Such efforts have become an integral element of the marketing strategies used by many firms. Concerns have been raised, however, that for some companies, this is little more than ‘greenwashing’, i.e. a cynical attempt to boost sales without any meaningful underlying sensitivity or change, in practice. Given the extremely negative track record of the global tobacco industry (Big Tobacco), it is essential that health policy makers and anti-smoking campaigners closely monitor this industry’s attempts to exploit both growing environmental concerns among consumers and gaps in legislation. Although there is relatively strong legislation in some countries, to prohibit suggestions that cigarettes may be environment friendly, a further tightening of legislation is required.